SARS-CoV2 and Co-Infections: A Review of Two Cases - Sumit Sohal; Guillermo Rodriguez-Nava; Ramzy Khabbaz; Sana Chaudry; Clio Musurakis; Solab Chitrakar; Vishnu V. Chundi; Harvey J. Friedman (Case Reports in Infectious Diseases)
COVID-19 infection caused by SARS-CoV2 virus is an acute respiratory illness which was declared as a pandemic by the World Health Organization. Usually, SARS-CoV2 infects independently and can cause spectrum of disease ranging from mild illness to severe progressive pneumonia, multiorgan dysfunction, and death; however, co-infections with other respiratory pathogens have been noted. Here, we present 2 fatal cases with co-infection, one with parainfluenza-4 virus and other co-infection/secondary infection with Streptococcus pneumoniae bacteria. Further studies are needed to study the effect of co-infections on morbidity and mortality of patients and establish the outcome of such infections.